Pengaruh Tax Planning, Profitabilitas, dan Likuiditas terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi (Studi Kasus Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Aji, Andri Waskita; Atun, FItri Fahmi (Universitas Pendidikan Ganesha, 2019)
The effect of tax planning, profitability, and liquidity on firm value with company size as a moderating variable. This study aims to determine the effect of tax planning, profitability, and liquidity on company value which is moderated by company size. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The population in this study were 141 companies and the samples obtained were 55 companies using purposive sampling techniques. Data testing methods used are multiple linear analysis and the method of moderate regression analysis (MRA). The test results show that tax planning has no positive effect on company value. Profitability has a positive influence on firm value. Liquidity variables have a negative influence on firm value. After the size of the company as a moderating variable, tax planning has a stronger negative effect on firm value. Profitability has a negative effect on firm value and company size is not able to strengthen the relationship. The liquidity variable is strengthened by the size of the company which can negatively influence the value of the company.